Characterization of braided river-delta facies in the Tarim Basin Lower Cretaceous: Application of borehole image logs with comparative outcrops and cores. (November 2018) - Nian, Tao; Jiang, Zaixing; Wang, Guiwen; Xiao, Chengwen; He, Wenjun; Fei, Liyin; He, Zhibo
Abstract: Borehole electrical image log with core-like presentation is an efficient way to conduct sedimentary description in the subsurface. The key is to set up a series of geological diagnostic criteria. The subsurface Lower Cretaceous Bashijiqike Formation in the Kelasu belt, Kuqa Depression, described as a sedimentary facies of braided river-delta front, has measured a mass of borehole image logs and open-hole logs at depths more than 6000 m. Combined with comparative outcrops, limited cores and thin sections, high-quality borehole images were fine calibrated to reveal their sedimentary details, with the aim of subtle sedimentary interpretation in the uncored intervals. The image elements all have corresponding geological indications. The lithologies are interpreted including mudstones, siltstones, fine- and medium sandstones and conglomerates, and the sedimentary structures are interpreted in terms of various bedding types, scoured surface and stacking modes. Thus, interdistributary bay, sandy or conglomerate subaqueous distributary channel and channel mouth bar are interpreted based on the lithologies, sedimentary structures and textures, basal and top contacts and succession variations. Furthermore, determination of paleo-current direction using borehole image logs is proposed for some time, but is far from mature and need to consider tectonic deformation settings of studied stratigraphy. Based on this, the paleo-current in the Kelasu belt is interpreted to flow southward from the Southern Tianshan to the depression during the Early Cretaceous which is consistent with the results derived from the heavy mineral analysis. However, the subaqueous distributary channels could frequently migrate locally and the paleo-current direction changed at localities with an offset angle varied between 30° and 150°. Regionally, the scale of single sand-body decreases lakeward and the sand-body may stretch at a maximum distance of 685.1 m along the flow direction. The diagnostic criteria and the workflow for borehole image interpretation in this study will have potential application to subsurface sedimentary description and guide sedimentary architecture where cores are not available. Highlights: A river-delta was characterized by imaging log with comparative outcrop and core. Structural dip removal must take into account deformation setting. Borehole images can fine determine depositional evolution over a depth interval. The workflow can guide quantitative sedimentary characterization in the subsurface.